Influences of Product Temperature on Emotional Responses to, and Sensory Attributes of, Coffee and Green Tea Beverages - Pramudya, Ragita C.; Seo, Han-Seok (Frontiers in Psychology, 2018)
Coffee and green tea are popular beverages consumed at both hot and cold temperatures. When people consume hot beverages concurrently with other activities, they may experience at different temperatures over the period of consumption. However, there has been limited research investigating the effects of product temperatures on emotional responses and sensory attributes of beverages. This study aimed to determine whether emotional responses to, and sensory attributes of, brewed coffee and green tea vary as a function of sample temperature. Using a check-all-that-apply (CATA) method, 157 participants (79 for coffee and 78 for green tea) were asked to evaluate either coffee or green tea samples served at cold (5 °C), ambient (25 °C), and hot (65 °C) temperatures with respect to emotional responses and sensory attributes. The results showed that sample temperature could have significant influences on emotional responses to, and sensory attributes of, coffee and green tea samples. More specifically, 6 and 18 sensory attributes of coffee and green tea samples, respectively, significantly differed with sample temperature. Beverage samples evaluated at 65 °C were characterized, regardless of activation/arousal level, by positive emotional responses terms and favorable sensory attributes. While beverages evaluated at 25 °C were associated more with negative emotional responses with low activation/arousal, those evaluated at 5 °C were more frequently characterized as having negative emotional responses with high activation/arousal. Sensory and emotional drivers of liking for both coffee and green tea differed both with sample temperature and gender. While both emotional responses and sensory attributes were identified as drivers of liking among females, only emotional responses were identified as drivers of liking among males. In conclusion, this study provides empirical evidence that both emotional responses to, and sensory attributes of, coffee and green tea beverages can vary with sample temperatures. To provide a better understanding of product characteristics, emotional responses to, and sensory attributes of, coffee or green tea beverages should be tested over a wider range of product temperatures.